Mathematical Creative Thinking Ability in terms of Mathematical Disposition in Creative Problem Solving Learning with an Open Ended Approach - Munafiah, Siti; Rochmad, Rochmad; Dwijanto, Dwijanto (Unnes Journal of Mathematics Education Research, 2021)
This study aims to describe students' mathematical creative thinking skills based on mathematical dispositions in creative problem solving learning with an open-ended approach. This research is a mixed method research with a sequential explanatory model. The population in this study were students of class VIII SMP N 3 Pabelan Semarang Regency in the academic year 2020/2021 with a sample of class VIII A and class VIII C as the experimental class and the control class. The research subjects were two students each with high mathematical disposition, medium mathematical disposition and low mathematical disposition. The results showed that students' creative thinking skills in each category of disposition had similarities and differences. All disposition categories have fulfilled the fluency aspect. On the flexibility aspect, only students with high disposition category are fulfilled. Subjects with a low disposition category can only fulfill one and two aspects of creative thinking abilities.